WAWANCARA KLINIS MENGGUNAKAN BAHASA MADURA UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK TENTANG HUKUM ARCHIMEDES - Lili Budiyarti; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to calculate the percentage of students’ misconceptions reduction based on the level of knowledge and the effectiveness of remediation using clinical interviews in the Madurese language about Archimedes’ law in teaching Physics at MTs Arrahman Sungai Raya. This research method was Case Study. The participants in this study were 9 students who were divided into three groups of students knowledge levels, high, medium, and low. The “paper pencil test” with three options was used as instrument of this study. Based on data analysis, there were obtained that the average percentage of students’ misconceptions reduction based on high, medium, and low knowledge levels were 87.5%; 64.6%; and 68.8%. The average of reduction in percentage in the number of misconceptions of all students after being remedied was 48.5%. Based on the calculation of effectiveness (∆S) shows that clinical interviews using the Madurese language are effective in remediating misconceptions about Archimedes law for the eighth grade students of MTs Arrahman Sungai Raya with an ∆S as 0.86 (high category: ∆S > 0.7).Keywords: Clinical Interview, Mother Language, Archimedes Law